Burden of musculoskeletal disorders in the gulf cooperation council countries, 1990–2019: Findings from the global burden of disease study 2019 - Alzahrani, Hosam; Alshehri, Mansour A.; Alotaibi, Mazyad; Alhowimel, Ahmed; Alodaibi, Faris; Alamam, Dalyah; Zheng, Yan; Tyrovolas, Stefanos (Frontiers in Medicine, 2022)
Abstract Objective: The purpose of this study was to investigate the burden of musculoskeletal (MSK) health conditions in Gulf Cooperation Council (GCC) countries based on the Global Burden of Disease (GBD) data. Methods: The data for GCC countries were obtained from the GBD study 2019 to evaluate the burden of MSK disorders which include the following countries: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates (UAE). The main outcome measures were age-standardized prevalence and years of life lived with disability (YLDs) associated with MSK disorders. The burden of MSK disorders attributable to the category of behavioral, metabolic or environmental/occupational was reported to estimate the risk-attributable fractions of disease. Results: MSK disorders prevalence ranked fifth in Kuwait, sixth in Bahrain, Oman, Qatar and UAE, and seventh in Saudi Arabia among all the diseases in 2019. For all GCC countries, MSK disorders were ranked the second leading cause of disability as measured by YLDs for the years 1990 and 2019. The age-standardized prevalence of MSK disorders in 2019 for Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and UAE was 18.56 (95% UI: 17.51–19.66), 19.35 (18.25–20.52), 18.23 (17.14–19.36), 18.93 (17.81–20.06), 19.05 (17.96–20.22) and 18.26 (17.18–19.38), respectively. The age-standardized YLDs per 100,000 individuals of MSK disorders in 2019 for Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and UAE were 1,734 (1,250–2,285), 1,764 (1,272–2,322), 1,710 (1,224–2,256), 1,721 (1,246–2,274), 1,681 (1,207–2,235) and 1,715 (1,230–2,274), respectively. For risk factors, high body mass index (BMI) had the highest contribution in MSK disorders YLDs in most GCC countries (Bahrain, Kuwait, Oman and Saudi Arabia), followed by exposure to occupational ergonomic factors which had the highest contribution in MSK disorders YLDs in Qatar and UAE. Conclusion: There was an increase in both age-standardized prevalence of MSK disorders and YLDs between 1990 and 2019 that was observed for all GCC countries. Some risk factors such as higher BMI and exposure to occupational ergonomic factors were highly associated with YLDs due to MSK disorders. The results of this study provide guidance for the potential nature of preventative and management programs to optimise the individual’s health.